Meeting the Needs of Pupils with Asperger Syndrome - McKernan, Des (REACH: Journal of Inclusive Education in Ireland, 1996)
About three in every hundred children may be affected by Asperger syndrome - a complex brain disorder related to autism. These children may appear to be 'odd but close to normal' in the ordinary classroom. Because they may function well academically, their particular needs may not be adequately addressed.